(untitled) (Marketing Journal, 2025)
This article provides an in -depth analysis of the organizational and economic factors influencing the formation of a regional governance system for managing soci o- economic development. It examines the pressing issues in improving the regional governance system under the conditions of Uzbekistan and evaluates existing problems from a scientific perspective. The study focuses on organizational and economic factors that contribute to enhancing the efficiency of regional governance, including the distribution of powers among state authorities, optimization of governance mechanisms, effective allocation of financial resources, and expansion of the independence of local self-government bodies. Furthermore, the condition of the regulatory and institutional framework necessary to ensure competitiveness in the regional economy is analyzed. Based on the conducted analysis, scientifically grounded proposals and recommendations have been developed to eliminate existing economic and organizational problems in regional governance and to create effective mechanisms for the use of resources.